(untitled) (Update Dental College Journal, 2016)
Corticosteroids, since their introduction have become one of the most widely prescribed class of drugs. They belong to a class of chemicals that includes steroid hormones that are produced naturally in the adrenal cortex of vertebrates and analogous to those that are synthesized in laboratories. They have been used extensively in managing many oral lesions due to their excellent anti-inflammatory and immunemodulators effects. However, considering their potential and significant side effects, they are sometimes termed as the double edge sword in the field of medicine. Their successful use depends upon the comprehension of the disease process. This includes an appropriate diagnosis, a clear view of the desirable treatment outcome and understanding of whether the treatment is aimed at the management of a chronic disease or enhanced resolution of a short term condition. The possible side effects of systemic corticosteroids must be weighed against probable risks. This article is aimed at reviewing the use of corticosteroids in the treatment of various oral lesions, and deriving a certain protocol for the same. Update Dent. Coll. j: 2016; 6 (1): 52-58